Exploring and Developing an Industrial Automation Acceptance Model in the Manufacturing Sector Towards Adoption of Industry 4.0 - Abu Bakar, Muhammad Ramzul; Razali, Noor Afiza Mat; Wook, Muslihah; Nazri Ismail, Mohd; Sem-Bok, Tengku Mohd Tengku (Manufacturing Technology Journal, 2021)
Technological progress in the 21st century has catalysed the industrial revolution (Industry 4.0) following the development of multiple new industrial automation technologies in the manufacturing sector. Regardless, past research indicated the unsuccessful attempts in adopting Industry 4.0 technologies among manufacturing organisations. Undoubtedly, the operationalisation of Industry 4.0 in manufacturing proved challenging as organisations were required to evaluate various aspects for effective implementation. Thus, a sound understanding of constructs concerning employees' acceptance and readiness levels towards novel automation technologies was required. Hence, this study aims to explore, develop, and validate the suggested conceptual framework by integrating the Technology Acceptance Model (TAM) and Technology Readiness Index (TRI) with Exploratory Factor Analysis (EFA). The EFA process was the first crucial step in ensuring the internal consistency and stability of the instrument across the sampling population. Consequently, the research outcome potentially enabled the manufacturing sector to identify and comprehend the key determinants in designing industrial automation technologies. This study also contributed to knowledge on technology acceptance by synthesizing TAM 3 and TRI 2.0 theories, thus constructing a new TAM in manufacturing.
Keywords: Industrial automation; Manufacturing; TAM; TRI; EFA